PENERAPAN MODEL PEMBELAJARAN SEARCH SOLVE CREATE AND SHARE (SSCS) UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI KELAS XI IPA SMA - Arief Maulana; K Anom Wancik; Sofia Sofia (Jurnal Penelitian Pendidikan Kimia: Kajian Hasil Penelitian Pendidikan Kimia, 2014)
The Application of Search Solve Create and Share (SSCS) Learning Model to Enhance the Elevent Grade Students’ Learning Outcome at Senior High School. The goal of study is to improve students’ learning outcome in chemistry through Search Solve Create and Share (SSCS) model at XI grade of IPA 2 SMA Negeri 1 Inderalaya. The model used in this study was classroom action research which was done in three cycles. The techniques of collecting the data in this study were observation sheet and final cycle test. The average of students’ learning outcome prior to the treatment (T0) was 57,81 with percentage of mastery learning (ML0) was 25%, (T1) = 66,55 and (ML1) = 82%, (T2) = 74,68 and (ML2) = 62,5%, (T3) = 80,15 and (ML3) = 87,5%.The result of study indicated that Search Solve Create and Share (SSCS) model could improve students’ chemistry learning outcome.